Impact of RCTs under Rice-Wheat cropping system in Indo- Gangetic Plains of India: A review - Kharia, Sushil Kumar; Goyal, Avinash; Jinger, Dinesh; Yadav, Brijesh (Annals of Agricultural Research, 2018)
The rice and wheat production practices are changing with the influence of several factors likewater availability, labour and climate conditions. Conversion from conventional agriculture toconservation agriculture may be efficient solution for maximizing grain production and supplyfood to growing population.Resource conservation practices (RCTs) such as direct seeding of rice,zero tillage of wheat, rice residue either as mulch or incorporated into the soil significantly improvedphysical, chemical as well as biological properties of soils. As a result, yield and yield attributingparameters also improved due to better soil conditions created by using RCT's. For improving thefarmers profitability in Indo-Gangetic Plains- a prototype shift is necessary. Based on experimentson different regions certain practice such as resources conserving practices are proposed to increasesystem productivity. Long term assessment of these practices under different climatic conditionswill reflect on efficiency of these practices.In this review, an attempt was made to highlight differentissues in rice-wheat system, which must be considered to develop policy for improving theproductivity and sustainability of this system.